Who Should Be at the Bedside 24/7: Doctors, Families, Nurses? - Gershengorn, Hayley B.; Garland, Allan (Seminars in Respiratory and Critical Care Medicine, 2016)
Critical illness does not keep to regular, daytime business hours; we must provide high-quality care and support for intensive care unit (ICU) patients 24 hours per day, 7 days per week. Whether this mandates the presence of similar numbers and types of personnel throughout all hours of the day, however, has been the subject of much debate and substantial research. In this article, we review the available literature on the consequences of having three groups of care providers at a patient's bedside overnight: physicians, visitors, and nurses. Though few of the studies on this topic are randomized and prospective, several themes have emerged from the existing data. First, there is dramatic variation in practice between and within countries. Second, the weight of evidence does not indicate that patient outcomes are improved by having an intensivist present overnight in ICUs that are staffed by intensivists during the daytime hours. Third, although visitation is highly restricted in many ICUs—out of concerns for disruption of care and a negative physiological or psychological impact on patients—the available data suggest that patients and their families generally benefit from open visitation policies. And finally, although there is little debate that nurses are (and should be) available in the ICU 24/7, existing data do not provide much of a consensus about the details. Uncertainties include whether outcomes are better when each nurse is assigned only one patient (or, more generally, the optimal patient:nurse ratio), who these nurses should be (e.g., registered nurses vs. other personnel), and what their roles should entail (e.g., managing ventilators). As such, we cannot yet identify the optimal overnight nurse staffing strategy. What is clear is that the critical care community needs more and better data to further define these aspects of the relationship between ICU structure and ICU outcomes.
Keywords: critical care; intensive care unit; optimal staffing; outcomes; intensivists; ICU telemedicine